UPPER PENNSYLVANIAN AGE OF THE LOWER TALCHIR FORMATION IN THE WARDHA BASIN, CENTRAL INDIA, BASED ON GUIDE PALYNOMORPHS PRESENT IN RADIOMETRICALLY- DATED PALYNOZONATIONS IN SOUTH AMERICA, AFRICA, AND AUSTRALIA (Ameghiniana, 2022)
This addendum is published to validate the proposed combination in Ameghiniana 58(4):326 following Art. 41.5 of the International Code of Nomenclature for algae, fungi, and plants (Shenzhen Code, Turland et al., 2018)). The new combination Cristatisporites conatus was first proposed by Kavali et al. (2021) but was not validly published as it was introduced without the full and direct reference (with page or plate) of the basionym.